The Murchison Widefield Array Commissioning Survey: A Low-Frequency Catalogue of 14 110 Compact Radio Sources over 6 100 Square Degrees. (2014) - Hurley-Walker, Natasha; Morgan, John; Wayth, Randall B.; Hancock, Paul J.; Bell, Martin E.; Bernardi, Gianni; Bhat, Ramesh; Briggs, Frank; Deshpande, Avinash A.; Ewall-Wice, Aaron; Feng, Lu; Hazelton, Bryna J.; et al.
Abstract: We present the results of an approximately 6 100 deg 2 104–196 MHz radio sky survey performed with the Murchison Widefield Array during instrument commissioning between 2012 September and 2012 December: the MWACS. The data were taken as meridian drift scans with two different 32-antenna sub-arrays that were available during the commissioning period. The survey covers approximately 20.5 h < RA < 8.5 h, − 58° < Dec < −14°over three frequency bands centred on 119, 150 and 180 MHz, with image resolutions of 6–3 arcmin. The catalogue has 3 arcmin angular resolution and a typical noise level of 40 mJy beam − 1, with reduced sensitivity near the field boundaries and bright sources. We describe the data reduction strategy, based upon mosaicked snapshots, flux density calibration, and source-finding method. We present a catalogue of flux density and spectral index measurements for 14 110 sources, extracted from the mosaic, 1 247 of which are sub-components of complexes of sources.